Read_Me. - Flagan, Are (Afterimage)
Highlights the H2K2 conference of the Hackers On Planet Earth which was held at the Hotel Pennsylvania in New York City from July 12 to 14, 2002. Speakers and topics discussed at the conference; Information on computer hacking; Several proposals that were presented to integrate a hacker ethic into the school curriculum from a K-12 level; Views of hackers about computers and technology.